Influence of AlN etching process on MISFET structures. Issue 3 (1st July 2019) - Firek, Piotr; Stonio, Bartłomiej
Abstract : Purpose: The purpose of this paper is to present the influence of gate dielectric etching on obtained MISFET (metal insulator semiconductor field effect transistor) structures. Because of its properties, aluminum nitride (AlN) layers can be successfully used in a large area of applications. In addition, AIN has a wide bandgap (6.2eV) and high thermal conductivity (3.2 W/cm * K). Its melting temperature is greater than 2, 000°C. The relative permittivity is about 9. All these features (especially high power, high temperature and high-frequency) make AlN a useful material in the fields of electronic, optical and acoustic applications. Design/methodology/approach: To fabricate n -channel transistors, silicon technology was used. The 50-nm thick AlN films were deposited using the magnetron sputtering. After preparation of SiO2 /AlN stack as the gate dielectric, the optimization processes of dry etching in plasma environment by Taguchi method were realized. In the next step, three methods of AlN etching were selected and used to MISFET device fabrication. Atomic force microscopy and scanning electron microscopy allowed to surfacing of the state observation after etching process. The current–voltage (I–V) output and transfer characteristics of structures with modified etch technology were measured. Keithley SMU 236/237/238 measurement set was used. Findings: In this research work, a method of AlN etching in a field effect transistor technology was developed and improved. Current−voltage characteristics of obtained MISFET structures were measured and compared. Influence of etching procedure on transistors properties was examined. Originality/value: The obtained results allow improving the MISFET technology based on AlN film as a gate dielectric. The complete research work will allow using the developed technologies to implement in highly sensitive ion-sensitive field effect transistor (ISFET) structures in the future. The improvement of the etching element in the technology strongly influences the detection capabilities and operating range of the transistor.